The Formation of Students’ Ecospirituality through Islamic Value Integration in Environmental-Based Islamic Boarding School Education - Abdul Rosyid; Ahmad Ihwanul Muttaqin (Journal of Educational Management Research, 2026)
This study aims to examine the nature of ecospirituality within Islamic education, the strategies for integrating Islamic educational values into an ecopesantren program, and the implementation of these values in shaping students’ spirituality and ecological awareness. The research employed a qualitative design with a phenomenological approach to explore participants’ lived experiences through non-participant observation, semi-structured interviews, and documentation analysis. Data were analyzed using the interactive model of data condensation, data display, and conclusion drawing, while triangulation techniques were applied to ensure credibility and trustworthiness. The findings indicate that ecospirituality is constructed through the systematic integration of theological principles, thematic curriculum development, contextual interpretation of religious texts, exemplary leadership, and structured environmental habituation programs such as cleanliness movements, room inspections, and waste-free initiatives. These practices transform environmental care into a lived spiritual commitment, fostering ecological consciousness alongside religious devotion. The study implies that faith-based environmental education can function as an integrative model that bridges Islamic pedagogy, spirituality, and sustainability in responding to contemporary ecological challenges.